Clinical‐instrumental and morphological evaluation of the effect of autologous dermal fibroblasts administration. (19th December 2014) - Zorin, Vadim; Zorina, Alla; Cherkasov, Vladimir; Deev, Roman; Kopnin, Pavel; Isaev, Artur
Abstract: Basic molecular mechanisms, associated with the main cell population of the dermis – fibroblasts – are the basis of skin aging. The number of functionally active fibroblasts in the skin and their biosynthetic activity decreases with age, thus enhancement of their cell density with synthetically active cells is accepted as a one of the most effective methods. The objective of the present study was to evaluate the safety and effectiveness of intradermal administration of autologous dermal fibroblasts in a year after treatment of 17 patients, aged 45–65 years. Results obtained with modern instrumental skin diagnostic methods (vacuum cutometry, optical profilometry, VISIA photometric analysis, etc.) demonstrate the safety and clinical effectiveness of dermal autofibroblast therapy: after transplantation, cultured autofibroblasts keep their biosynthetic activity and produce extracellular matrix for at least 12 months. As a result, remodelling of the dermis microstructures is observed, accompanied by a progressive increase of collagen content and thickness of the dermis (up to 62.5 ±6.7% in 12 months). This is clinically expressed by increase of skin elasticity (24.0 ±4.3% in periorbital area) and thickness of the skin, and by decrease in the number and depth of wrinkles (46 ±7% by the end of observation period). Copyright © 2014 John Wiley & Sons, Ltd.